CUSTOMER BRAND RELATIONSHIP: PERAN BRAND LOVE TERHADAP BRAND COMMITMENT DAN POSITIVE WORD OF MOUTH - Clara, Catharina (Jurnal Bulletin, 2019)
The purpose of this study is to find out how customer brand relationship, wheter strong consumer brand love influences willingness to spread positive word of mouth directly or Â through brand commitment. This research is a survey research, conducted in 5 cinema locations in Palembang. The analysis method uses mediated regression analysis. So the results of this study can explain whether brand love influences brand commitment and willingness to spread positive word of mouth.